Process Simulation on Fast Pyrolysis of Palm Kernel Shell for Production of Fuel - Nayaggy, Mangala; Putra, Zulfan Adi (Indonesian Journal of Science and Technology, 2019)
As the worlds primary source of energy is depleting, an alternative particularly renewable energy is being explored. This work is a preliminary study on fast pyrolysis process of palm kernel shell to produce liquid fuel. The simulation uses pyrolysis data obtained from one of the previous works on fast pyrolysis of palm kernel shell. As there are no literature available on upgrading of bio oil from fast pyrolysis of palm kernel shell, the chemical reactions are synthesised based on upgrading of bio oil from different biomass. The upgraded oil is then analysed by comparing its distillate curve with that of the ASTM of gasoline. The distillation curves are shown to be quite similar as the components found in the oil almost resemble those in the gasoline. Thus, the bio oil from fast pyrolysis of palm kernel shell has almost similar components compared to the ASTM of gasoline.